The suffering relief from chronic ill as a focus in nursing care - Batista, Susana; Martins, Rosa (Servir, 2016)
Introduction Understand and relieve human suffering must be assumed as fundamental elements of care, constituting even a moral and ethical duty for nurses. Objectives To know the chronic ill´s perception on nursing care in suffering relief as well as the coping strategies used. Methods This is a non-experimental, cross-sectional descriptive- correlational and triangulated study, used in a non- probabilistic convenience sample of 307 chronically ill patients. Data were collected through a questionnaire between January and June 2013 to chronic ill, hospitalized or in treatment on an outpatient basis in the hospital. It was requested the permission of hospital ethics committee, as well as the informed consent of each participant. Data processing was performed statistically and content analysis. Results For 74.2% of the patients, care effected by nurses significantly relieves their suffering, being this relief related to the “availability, willingness to help, dedication and attention demonstrated” by these professionals. The coping strategy with greater impact on suffering relief is related to the “care and family company” (62.4%). The suggestions presented to improve nursing practice are in order of importance: more affection, sympathy, interest, fast service, more time, and respect for the dignity, common sense and more communication / information. Conclusions For 74.2% of the patients, care effected by nurses significantly relieves their suffering, being this relief related to the “availability, willingness to help, dedication and attention demonstrated” by these professionals. The coping strategy with greater impact on suffering relief is related to the “care and family company” (62.4%). The suggestions presented to improve nursing practice are in order of importance: more affection, sympathy, interest, fast service, more time, and respect for the dignity, common sense and more communication / information.